Analysis of 94 Candidate Genes and Twelve Endophenotypes for Schizophrenia from the Consortium on the Genetics of Schizophrenia - Greenwood, Tiffany A. (2011)
OBJECTIVE: We have used a custom 1,536-SNP array to interrogate 94 functionally relevant candidate genes for schizophrenia and identify associations with 12 heritable neurophysiological and neurocognitive endophenotypes collected as part of the Consortium on the Genetics of Schizophrenia (COGS). METHOD: Variance-component association analyses of 534 genotyped subjects from 130 families were conducted using Merlin. A novel bootstrap Total Significance Test was also developed to overcome the limitations of existing genomic multiple testing methods and robustly demonstrate the presence of significant associations in the context of complex family data and possible population stratification effects. RESULTS: Associations were observed for 46 genes of potential functional significance with 3 SNPs at p<10(−4), 27 SNPs at p<10(−3), and 147 SNPs at p<0.01. The bootstrap analyses confirmed that the 47 SNP-endophenotype combinations with the strongest evidence of association significantly exceeded (p=0.001) that expected by chance alone with 93% of these findings expected to be true. Many of the genes interact on a molecular level, and eight genes displayed evidence for pleiotropy (e.g., NRG1 and ERBB4), revealing associations with four or more endophenotypes. Our results collectively support a strong role for genes related to glutamate signaling in mediating schizophrenia susceptibility. CONCLUSIONS: This study supports the use of relevant endophenotypes and the bootstrap Total Significance Test for the identification of genetic variation underlying the etiology of schizophrenia. In addition, the observation of extensive pleiotropy for some genes and singular associations for others in our data suggests alternative, independent pathways mediating pathogenesis in the “group of schizophrenias”.